Generating 10-40 MeV high quality monoenergetic electron beams using a 5 TW 60 fs laser at Tsinghua University - 华剑飞 颜立新 白植豪 张超杰 李飞 万阳 吴益鹏 徐新路 杜应超 黄文会 陈怀壁 唐传祥 鲁巍 (Chinese physics C, 2015)
A unique facility for laser plasma physics and advanced accelerator research has recently been built at Tsinghua University. This system is based on a Tsinghua Thomson scattering X-ray source （TTX）, which combines an ultrafast TW laser with a synchronized 45 MeV high brightness linac. In our recent laser wakefield acceleration experiments, we have obtained 10-40 MeV high quality monoenergetic electron beams by running the laser at 5 TW peak power. Under certain conditions a very low relative energy spread of a few percent can be achieved. Absolute charge calibration for three different scintillating screens has also been performed using the linac system.